The modern math movement(s): an essay on how elementary school teachers in Brazil gave meaning to it - Souza, Luzia Aparecida de; Garnica, Antonio Vicente Marafioti [UNESP] (Clame-comite Latinoamericano Mat Educ, 2013)
The main goal of this paper is to discuss the production of meaning of the Modern Math Movement. The main sources were data available in school archives and interviews with former teachers that we use in order to focus on the diversity of perspectives -that complement it or oppose it-, which comes up when teachers refer to the Movement. Using this process of signification, teachers whether accept it, invalidate it or adapt it to guidelines imposed to them in their teaching activities. We establish a methodology by following the premises of Oral History to gather oral testimonies. The theoretical foundations in which this article is written are the guidelines of Paul Ricoeur's Hermeneutics, John Thompson's Depth Hermeneutics and Bolivar's narrative analysis.
Keywords: Modern Maths; Attribution of meanings; Appropriation/mobilization; History of Mathematics Education; Basic Education